2021
DOI: 10.5194/esurf-9-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater erosion of coastal gullies along the Canterbury coast (New Zealand): a rapid and episodic process controlled by rainfall intensity and substrate variability

Abstract: Abstract. Gully formation has been associated to groundwater seepage in unconsolidated sand- to gravel-sized sediments. Our understanding of gully evolution by groundwater seepage mostly relies on experiments and numerical simulations, and these rarely take into consideration contrasts in lithology and permeability. In addition, process-based observations and detailed instrumental analyses are rare. As a result, we have a poor understanding of the temporal scale of gully formation by groundwater seepage and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Headward retreats in the formation of gullies is a well-known process, which according to some is related to landslides, especially in the case of intense rainfall, as observed for example in volcanic soil in Ethiopia [16,17,75], in saprolites of various lithologies in Madagascar [13,76,77] or in fluvio-deltaic deposits as in New Zealand [78]. Nevertheless, these processes are often related to internal erosion [13,18,52,76,79,80].…”
Section: Headward Retreats and Gully Formationmentioning
confidence: 99%
“…Headward retreats in the formation of gullies is a well-known process, which according to some is related to landslides, especially in the case of intense rainfall, as observed for example in volcanic soil in Ethiopia [16,17,75], in saprolites of various lithologies in Madagascar [13,76,77] or in fluvio-deltaic deposits as in New Zealand [78]. Nevertheless, these processes are often related to internal erosion [13,18,52,76,79,80].…”
Section: Headward Retreats and Gully Formationmentioning
confidence: 99%
“…Seepage erosion has been studied at different spatial scales as a form of channel development. At large scales, seepage erosion has been attributed as the primary driver of channel development for drainage networks in unconsolidated materials (Coelho Netto et al, 1988;Micallef et al, 2021;Pillans, 1985;Schumm and Phillips, 1986;Uchupi and Oldale, 1994), and in bedrock in places like the Colorado Plateau (Howard, 1988;Laity and Malin, 1985) and Florida Panhandle (Schumm et al, 1995). The channel heads of these networks are often described as "amphitheater-shaped" due to the distinctive high relief headwalls that form when seepage erosion undermines channel headwalls and causes mass wasting (Laity and Malin, 1985), although this morphology may arise from any curvature-driven mechanical process (Petroff et al, 2018).…”
Section: Processes Of Channel Developmentmentioning
confidence: 99%
“…The degree to which drainage networks develop by overland flow or seepage erosion depends on a number of factors including substrate, rainfall rate, and relief. Field studies in unconsolidated sands and gravels have found that groundwater seepage can play an important role in channel development and formation (Coelho Netto et al, 1988;Dunne, 1990;Lapotre and Lamb, 2018;Micallef et al, 2021;Pillans, 1985;Schumm et al, 1995;Schumm and Phillips, 1986;Uchupi and Oldale, 1994). As…”
Section: Process Drivers: Substrate Precipitation Reliefmentioning
confidence: 99%
See 1 more Smart Citation
“…In subaerial settings, fluid seepage has been shown to unambiguously lead to the formation of box canyons only in unconsolidated sand to gravel sized sediments (Lapotre & Lamb, 2018; Lobkovsky et al., 2007; Micallef et al., 2021; Schumm et al., 1995). The efficacy of fluid seepage as an erosive agent in bedrock remains disputed, however, and there is no unambiguous example of a bedrock box canyon formed by seepage erosion (Lamb et al., 2006).…”
Section: Introductionmentioning
confidence: 99%